Crecimiento radial del corcho de reproducción de los alcornocales catalanes y valencianos - Fos, S.; Barreno, E. (Scientia gerundensis, 1994)
Eastern cork-oak forests are present in territories with different environmental characteristics, allowing to raise comparative studies between them. This work is an attempt to evaluate the radial growt differences of the reproduction cork, using tschniques of optical microscopy, having developed a new methodology. Thus, severa1 sites from catalonian and valencian cork-oak forests have been selected. In the quantification of this growth, the contribution of each cork type (early cork and late cork) in the annual growing rings have been differentia- ted. The annual increments measwed in catalonian corks have an average of 2.958 mm, being a bit lower in Castell6n with 1.622 mm. These differences in the annual growing rings are due to the early development higher in catalonian cork (2.623 mm) than in valencian ones (1.235 mm), late cork thickness is similar in the two areas. These differences seem to be related with the escarce summer dry period in catalonian cork-oak forests. Important anato- mical differences related with the mentioned ombroclimatic asimetries have been observed too.
Keywords: Anatomy; bioclimatology; cork-oak; Quercus suber L.; Radial growth